A systematic review of the role of surfactants in bronchial asthma: Implications for pathogenesis and treatment of the disease - Ismailov, Imetkul; Kılınç, Nihal; Kumar Magarde, Bhupendra; Musheer, Mohd; Ahmad, Shakil (Gaceta Médica de Caracas, 2024)
The study aims to examine existing literature and highlight the significance of surfactants as a factor in pathogenesis and a potential therapeutic target in bronchial asthma. A systematic search is conducted in Scopus, Web of Science, and PubMed/Medline, utilizing specific keywords related to surfactants and bronchial asthma. The findings demonstrate that surfactants, a unique mixture of lipids and proteins, play a crucial role in the mechanisms of innate and adaptive immunity in the lungs. They act as a mechanical barrier, modulate inflammatory responses, and interact with pathogens. Changes in surfactant composition and levels have been associated with various lung diseases, including bronchial asthma